2019
DOI: 10.1016/j.waojou.2019.100089
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of managing food allergy in the developing world

Abstract: Food allergy (FA) is currently a significant health care problem in the developing world. Widely varying study populations and methodologies, the use of surrogate markers such as self report or hospitalization rates due to anaphylaxis rather than objective methods, limits robust estimation of FA prevalence in low income settings. Also, allergy is under-recognized as a clinical specialty in the developing world which compromises the chance for accurate diagnosis. In this review, most published data on food alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 162 publications
1
63
0
Order By: Relevance
“…Furthermore, in relation to the eating habits, different foods may also be responsible for allergic sensitization in other countries. For example, school-age Mexican children more often exhibit hypersensitivity reactions to chocolate, strawberries, crustaceans, and eggs [32], while sensitization to nuts and peanuts is more common in Chile [33], to chili, walnuts, chocolate, milk, and prawnsin El Salvador [34], and to fruits, vegetables, and seafood in Colombia [35,36].…”
Section: Epidemiologymentioning
confidence: 99%
“…Furthermore, in relation to the eating habits, different foods may also be responsible for allergic sensitization in other countries. For example, school-age Mexican children more often exhibit hypersensitivity reactions to chocolate, strawberries, crustaceans, and eggs [32], while sensitization to nuts and peanuts is more common in Chile [33], to chili, walnuts, chocolate, milk, and prawnsin El Salvador [34], and to fruits, vegetables, and seafood in Colombia [35,36].…”
Section: Epidemiologymentioning
confidence: 99%
“…The prevalence of IgE-mediated cow's milk allergy (CMA) in infancy and early childhood has been estimated at 2-3% worldwide [2]. In Europe, a large cohort study confirmed challenge-proven cow's milk allergy in <1% of children up to 2 years old [3].…”
Section: Introductionmentioning
confidence: 99%
“…Food allergy is an increasing global health problem in both the developed and developing world. 12 , 13 In many Asian countries as in Japan, soybean is commonly consumed daily in large quantities and is also a major cause of food allergies. 11 FDEIA is mainly caused by foods, such as wheat and crustaceans.…”
Section: Casementioning
confidence: 99%